Answer: 12x + 6y= 120 and -24x -6y = -180
Explanation:
12x + 6y = 120
4x + y = 30
To eliminate one of the variables the coefficients have to have the same values but different signs.One has to be positive and one has to be negative then you could add them up to get become zero. So in the two systems of equations you can multiply the down equation by -6 to eliminate the y variable but the top equation will have to be the same.
-6(4x + y)=30(-6)
-24x -6y = -180
You can now rewrite the equation as
12x + 6y = 120
-24x -6y = -180 Now you can add the top and down equations to eliminate the y variable.